Differential ascending and descending aortic mechanics parallel aneurysmal propensity in a mouse model of Marfan syndrome. Issue 12 (16th August 2016) - Bellini, C.; Korneva, A.; Zilberberg, L.; Ramirez, F.; Rifkin, D.B.; Humphrey, J.D.
Abstract: Marfan syndrome (MFS) is a multi-system connective tissue disorder that results from mutations to the gene that codes the elastin-associated glycoprotein fibrillin-1. Although elastic fibers are compromised throughout the arterial tree, the most severe phenotype manifests in the ascending aorta. By comparing biaxial mechanics of the ascending and descending thoracic aorta in a mouse model of MFS, we show that aneurysmal propensity correlates well with both a marked increase in circumferential material stiffness and an increase in intramural shear stress despite a near maintenance of circumferential stress. This finding is corroborated via a comparison of the present results with previously reported findings for both the carotid artery from the same mouse model of MFS and for the thoracic aorta from another model of elastin-associated glycoprotein deficiency that does not predispose to thoracic aortic aneurysms. We submit that the unique biaxial loading of the ascending thoracic aorta conspires with fibrillin-1 deficiency to render this aortic segment vulnerable to aneurysm and rupture.